Nanocarriers: A Successful Tool to Increase Solubility, Stability and Optimise Bioefficacy of Natural Constituents - Bilia, Anna R.; Piazzini, Vieri; Risaliti, Laura; Vanti, Giulia; Casamonti, Marta; Wang, Meng; Bergonzi, Maria Camilla (Current Medicinal Chemistry, 2019)
Natural products are fascinating molecules in drug discovery for their exciting structure variability and also for their interaction with various targets. Drugs multi-targeting effect represents a more realistic approach to develop successful medications for many diseases. However, besides a large number of successful in vitro and in vivo studies, most of the clinical trials fail. This is generally related to the scarce water solubility, low lipophilicity and inappropriate molecular size of natural compounds, which undergo structural instability in biological milieu, rapid clearance and high metabolic rate. Additionally, some molecules are destroyed in gastric juice or suffer to a massive pre-systemic metabolism in the liver, when administered orally, limiting their clinical use. A reduced bioavailability can also be linked to drug distribution/accumulation in non-targeted tissues and organs that increase the side effects lowering the therapeutic efficacy and patient compliance. Nanomedicine represents a favourable tool to increase bioavailability and activities of natural products. Generally, nanovectors provide a large surface area and can overcome anatomic barriers. Each nanovector has its own advantages, disadvantages, and characteristics. In this review, different nanocarriers made of compounds which are Generally Recognized As Safe (GRAS) for the delivery of natural products, marketed as food supplements and medicines are reported.
Keywords: lipid-based and polymeric nanoparticles